Critical Biot Number of a Periodic Array of Rectangular Fins - Fyrillas, Marios M.; Leontiou, Theodoros (Journal of Heat Transfer, 2016)
We consider the heat transfer problem associated with a periodic array of rectangular fins subjected to convection heat transfer with a uniform heat transfer coefficient. Our analysis differs from the classical approach as (i) we consider two-dimensional (2D) heat conduction and (ii) the wall, to which the fins are attached, is included in the analysis.
Keywords: critical Biot number; fin effectiveness; heat convection; Heat transfer; optimum fin; rectangular fin; uniform heat transfer coefficient; Research Subject Categories::TECHNOLOGY::Engineering physics